Theoretical investigation of the power curve of small HAWT by combining aerodynamic and mechatronic systems - Chen, Yu‐Jen; Shiah, Yui‐Chuin; Tsai, Yi‐Lun; Chang, Chia‐Hsiang; Chen, Ming‐Huang (International journal of energy research, 2022)
Summary In this paper, a dynamic model is presented to analytically evaluate the power performance of small horizontal axis wind turbine (HAWT) by integrating all related theories in aerodynamics and mechatronics. This model is implemented into a computer program for predicting the output torque and power performance curve of small HAWT. In this implemented program, all pertinent formulations in the blade momentum theory (BEMT) and the Fleming's rule are combined together. For verifying the model, a small HAWT (rated 400 W) using an axial flux permanent magnet (AFPM) generator was experimented in a full‐scale wind tunnel. For a field test, the prototype was installed in National Penghu University International Small‐Medium Wind Turbine Site to collect data at various wind speeds in a whole month. The collected data turned out to agree with our prediction using the proposed model. In designing small HAWT, this model not only expedites the development process but also ensures safe operation of the complete system. For analytically evaluating the performance of small horizontal axis wind turbine (HAWT), the present work has integrated theories in the aerodynamics and Mechatronics to work out a dynamic model. This proposed model only takes about 5 minutes to model the dynamic performances of a system. By overcoming experimental difficulties, prediction of the implemented program using the dynamic model has been verified. For additional verification, outdoor tests were carried out to make comparisons with our predictions, showing consistence between the both.